Pelatihan Gizi dan Pembibitan Tanaman Rumah Tangga untuk Peningkatan Kualitas Gizi Keluarga - Yudita Ingga Hindiarti; Arifah Septiane Mukti; Siti Fatimah (Yayasan Inspirasi El Burhani, 2026)
Introduction: The stunting rate in West Java Province is higher than the national average and the highest of the 14 existing regions. Ciamis Regency, particularly Sindangkasih District, is among the highest (Health Office, West Java Province 2021). The process of stunting has been lasting since the pregnancy and it gets worse if it cannot be treated (catch-up growth) within the first 1000 days of life (1000 HPK). Low family awareness of nutrition will have an impact on the health and nutritional status of toddlers. Based on the research result related to stunting, knowledge-raising intervention for health cadres related to nutrition is very effective in increasing the practice of mentoring mothers of under-five toddlers. Therefore, it is necessary to increase cadres’ knowledge and understanding of locus stunting through nutrition training strategies and home plant cultivation as a preventive measure for the nutritional adequacy of under-five toddlers in 1000 HPK. Community service activities aim to realize community empowerment to use local food as the basis for sustainable home food. The targets in this community service are cadres and mothers of under-five toddlers. Objective: The purpose of this service was realize community empowerment to use local food as the basis for sustainable home food Method: The method of this community service uses nutrition training to increase the knowledge, capacity, and ability of village cadres and mothers of under-five toddlers regarding food diversification which is nutritious, balanced, and safe to consume as home plants. At the beginning of the activity, a pretest was carried out followed by the delivery of material, cooking demonstrations, and a post-test. Result: The results showed that there was a significant increase in mothers’ knowledge of under-five toddlers and cadres about the importance of nutrition in 1000 HPK. Conclusion: Nutrition training is a promotive activity, a basis for implementing other nutrition intervention programs, and a basis for a person's behavior.